KETERLIBATAN PEMERINTAH DAERAH DALAM PENCEGAHAN KONFLIK ATAS KEHADIRAN ALFAMIDI DI KABUPATEN KOLAKA - Muhammad, Alamsyah; Wa Ode, Sifatu; Elvianus Koodoh, Erens (Jurnal Penelitian Budaya, 2021)
This study aims to describe the conflict prevention efforts between UMKM retailers and Alfamidi in Kolaka Regency by the Kolaka Regency Government. The theory used in this research refers to Marx's concept, which focuses on conflicts that occur due to interactions that occur in the economic system; production sub-system, distribution sub-system, trade sub-system and consumption sub-system, then the solution is to harmonize these interactions by building new relationships that need each other and last a long time, in order to stem the factors that cause conflicts that can occur. . The method used in this research is descriptive qualitative method, with data collection techniques through observation, in-depth interviews and instrumentation. Based on the results and discussion, basically the types of conflicts that occur are goal and personal, where the factors that cause conflict are (1) communication, and (2) structure. And then the factors causing the conflict are dammed by; (1) Memorandum of Understanding is drawn up between the Local Government of Kolaka Regency and PT. Midi Utama Indonesia Tbk, (2) holding Alfamidi Exposure Socialization and (3) implementing promo prices for MSME retail owners as well as presenting Member Relation Officer by Alfamidi.Keywords: Alfamidi, conflict, economy, MSMEs, retail.